The effect of the 'M' Technique® massage on physiological parameters in preterm neonates: a randomized controlled trial study - Mona Alinejad-Naeini; Farshad Heidari-Beni; Parisa Mohagheghi; Soroor Sohrabi; Soraya Shojaee Jeshvaghanie (Hygeia Press di Corridori Marinella, 2022)
Introduction: Preterm birth is one of the major health problems in developed and developing countries. The 'M' Technique® is a gentle, structured, stroking relaxation massage technique, which aims to reduce stress in preterm neonates in the Neonatal Intensive Care Unit (NICU) that cannot tolerate conventional massage techniques. Evidence consistently suggests that the 'M' Technique® is a safe non-medical intervention. The aim of this study was to examine the effect of the 'M' Technique® on physiological parameters of preterm neonates admitted to the NICU. Methods: This study is a randomized controlled trial conducted on preterm neonates at a Level III NICU, affiliated to Iran University of Medical Sciences, from February 2018 to May 2019 in Tehran, Iran. The convenience sampling method was used. Physiological parameters were measured 5 minutes before, during and then 10 minutes after each intervention for 2 weeks. Data were analyzed using SPSS® version 23 for Windows® (SPSS Inc., Chicago, IL, USA).  Results: The findings showed there was no statistically significant difference between groups in heart rate, respiratory rate and oxygen saturation before intervention on the 1st day (p = 0.868, p = 0.399 and p = 0.677, respectively), but a statistically significant difference was observed during and after the intervention in heart rate (p = 0.011 and p < 0.001, respectively), respiratory rate (p < 0.001 and p < 0.001, respectively) and oxygen saturation (p = 0.002 and p = 0.001, respectively) in the same day. These results were repeated in the 7th and 14th days, too. Conclusion: The use of 7-minute 'M' Technique® for preterm neonates has a positive effect on physiological parameters and improves physiologic stability.